2011
DOI: 10.1258/acb.2010.010137
|View full text |Cite
|
Sign up to set email alerts
|

Effect of NT-proBNP testing on diagnostic certainty in patients admitted to the emergency department with possible heart failure

Abstract: Measurement of NT-proBNP concentrations reduces diagnostic uncertainty and improves diagnostic accuracy in patients presenting to the ED with dyspnoea and possible HF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(24 citation statements)
references
References 24 publications
0
24
0
Order By: Relevance
“…Specifically, an increased NT‐proBNP concentration was a stronger predictor of CHF than other variables evaluated including radiographic findings and clinical signs . In another study, the addition of BNP assay significantly increased diagnostic accuracy (from 53% to 71%) along with increased certainty (from 34% to 82%) in the assessment of people presenting to the emergency department for possible CHF. The additive value of NT‐proBNP testing to traditional diagnostic testing appears to be highest in cases in which diagnostic uncertainty is greatest .…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Specifically, an increased NT‐proBNP concentration was a stronger predictor of CHF than other variables evaluated including radiographic findings and clinical signs . In another study, the addition of BNP assay significantly increased diagnostic accuracy (from 53% to 71%) along with increased certainty (from 34% to 82%) in the assessment of people presenting to the emergency department for possible CHF. The additive value of NT‐proBNP testing to traditional diagnostic testing appears to be highest in cases in which diagnostic uncertainty is greatest .…”
Section: Discussionmentioning
confidence: 94%
“…The additional value of the NT‐proBNP assay as compared to traditional diagnostic tests such as physical examination, thoracic radiography, and serum biochemistry in individual cases has not been evaluated. In the emergency room setting in human medicine, information from BNP measurement combined with that obtained from clinical judgment increased diagnostic accuracy and decreased diagnostic uncertainty when evaluating dyspneic patients . Thus, we hypothesized that combining the NT‐proBNP assay with traditional diagnostic assessments (ie, history, physical examination, ECG, and thoracic radiography) would improve the accuracy and confidence of diagnoses made by general practitioners to discriminate between cardiac and noncardiac cause of respiratory distress in cats.…”
mentioning
confidence: 99%
“…5NT-proBNP is a product of the pro-hormone brain natriuretic peptide which is released by cardiac myocytes when the ventricles are subject to haemodynamic stress [26] and is the current serological diagnostic marker of heart failure [21]. There is now a large literature on 5NT-proBNP in heart failure, which has clearly demonstrated that a normal blood 5NT-proBNP excludes cardiac failure in 99% of cases [20,21]. We measured EBC 5NT-proBNP in EBC in acutely dyspnoeic patients, and found that ACPO group had the highest numerical mean value, as expected.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesised that some breath biomarkers would be raised in CAP but not in ACPO or in a matched control group, while EBC pH would be decreased [16][17][18][19]. We also measured EBC 5N-terminal probrain natriuretic peptide (5NT-proBNP), a marker of cardiac myocyte injury, which is raised in the peripheral blood in heart failure [20,21].…”
Section: Introductionmentioning
confidence: 99%
“…However, it may also reflect the fact that physicians are generally more likely to discharge mildly symptomatic patients but not the very symptomatic ones. Robaei et al 16 have shown in 68 patients presenting to the ED with dyspnoea and possible heart failure that NT-proBNP testing improved diagnostic accuracy, however, they did not report the effect on admission. It seems that in practice when older and sicker patients are concerned, such as those enrolled in the present study, uncertainty dictates the need to admit whether the problem is ADHF or not.…”
Section: Diagnosis Of Adhf In the Edmentioning
confidence: 97%